Tantangan dan Peluang Penerapan Teknologi Digital dalam Pengelolaan Biaya Operasional Usaha Jasa: Sebuah Tinjauan Pustaka - Nur Aznisyah; Masyhuri, Masyhuri (Journal of Economic and Business Advancement, 2026)
This study examines the challenges and opportunities associated with the implementation of digital technology in managing operational costs within service-based businesses through a qualitative library research approach. The findings indicate that digitalization has transformed operational management into integrated, data-driven, and real-time systems that support efficiency and organizational adaptability. Several barriers affecting implementation include limited digital literacy, organizational resistance, inadequate technological infrastructure, fragmented information systems, cybersecurity risks, and high initial investment costs. Digital technology also creates strategic opportunities through business process automation, integration of operational systems, real-time cost control, digital payment systems, and productivity enhancement, contributing to sustainable competitive advantage in the digital economy era.